The effect of Sea urchin (Diadema setosum) gonad extract on IgM and IgG antibodies production in BALB/c mice infected by Salmonella typhi - Wa Ode Salma; Ilyas Yusuf; Marni Karo; La Banudi (Jurnal Gizi Klinik Indonesia, 2018)
Background: Salmonella typhi infection decreases of the immune system and influences the adaptive antibodies among malnourished children. The gonad of Diadema setosum (D. setosum) is one of food sources from marine biota that contains high-quality nutrients and potentially can be used as a dietary supplement for typhoid fever condition.Objective: This study aimed to determine the effect of gonad D. setosum extract on the production of antibody IgM and IgG in an animal model.Method: This experimental study was used BALB/c mice before and after infected Salmonella typhi through intraperitoneally at 0.2 mL x the unit 103 CFU/mL. The level of IgM and IgG production was measured by Enzyme Linked Immune Sorbent Assay (ELISA). Experimental animals were divided into 2 groups. The control group was only fed with standard diets, while at the intervention group received the extract of D. setosum gonad in two doses (100 and 200 mg/kg body weight).Results: Production of IgM antibodies in the control group significantly increased twofold (p=0.001) whereas the intervention group received the extracts of D. setosum gonad (200 mg/kg body weight) could suppress the increase in IgM antibody production and indicate the highest increase of IgG antibody significantly (p<0.05) at day 7.Conclusion: The gonad of Diadema setosum extracts (200 mg/kg body weight) could suppress the increase in IgM antibody productions and indicate the highest increase of IgG antibody titers in mice infected with Salmonella typhi. The role of anti-microbial substances of the gonad of Diadema setosum, is potential to be utilized as dietary supplement to increase body immune system among patients infected by Salmonella typhi.